STUDYING AS A KIND OF CREATIVITY IN THE INITIAL SCHOOL - Babiy, Nikolai Fedorovich (Psychological Prospects Journal, 2013)
The article analyzes the results of empirical research on the disclosure of creative potential of junior pupils in educational activities. The determinants of low-level creativity discovery in children of this age category and ways to solve the problem are indicated.